Pelatihan Promosi Reseller Sambal Hiyung - Herlin Ellen Kurniawan; Wulanmeiaya Wowor (Journal of Community Service and Engagement, 2022)
Community Service is one of the tri dharmas of higher education that can be aimed at increasing a sense of concern for the community by sharing knowledge and skills. The objectives of this Community Service activity are: (1) providing training on Sambal Hiyung marketing (2) providing education about marketing through social media (3) building collaboration between the Faculty of Tourism, Pelita Harapan University and the SML UMKM Center (4) carrying out one of the functions Tri Dharma higher education, especially in the field of Community Service. Therefore, the Community Service team carried out training activities to provide training on Sambal Hiyung marketing in the form of online workshops to a number of SML MSME Center business actors digitally, based on the problems faced by SML MSME Center business actors who needed new products to increase their income by opening the opportunity to become a reseller. It is hoped that this activity can be useful for MSME Center business.